2004
DOI: 10.1007/s00122-004-1774-x
|View full text |Cite
|
Sign up to set email alerts
|

Tagging and mapping of a rice gall midge resistance gene, Gm8, and development of SCARs for use in marker-aided selection and gene pyramiding

Abstract: Using amplified fragment length polymorphisms (AFLPs) and random amplified polymorphic DNAs (RAPDs), we have tagged and mapped Gm8, a gene conferring resistance to the rice gall midge (Orseolia oryzae), a major insect pest of rice, onto rice chromosome 8. Using AFLPs, two fragments, AR257 and AS168, were identified that were linked to the resistant and susceptible phenotypes, respectively. Another resistant phenotype-specific marker, AP19(587), was also identified using RAPDs. SCAR primers based on the sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 26 publications
0
17
0
2
Order By: Relevance
“…Karena pita DNA selain target amplikon lain di RAPD juga muncul, maka modifikasi menjadi marka STS atau SCAR yang dikembangkan berdasarkan RAPD lebih dianjurkan. Marka STS berhasil dikembangkan dari AFLP dan RAPD untuk mengidentifikasi lokasi kromosom untuk gen ketahanan patogen pada padi (Jain et al, 2004). Primer STS hasil pengembangan dari RAPD yang telah digunakan untuk mengidentifikasi varietas padi premium Jepang, Koshihikari (Ohtsubo et al, 2002) dan galur isogeniknya (Nakamura et al, 2004), digunakan dalam penelitian ini dan diobservasi pada varietas padi japonica dan indica.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Karena pita DNA selain target amplikon lain di RAPD juga muncul, maka modifikasi menjadi marka STS atau SCAR yang dikembangkan berdasarkan RAPD lebih dianjurkan. Marka STS berhasil dikembangkan dari AFLP dan RAPD untuk mengidentifikasi lokasi kromosom untuk gen ketahanan patogen pada padi (Jain et al, 2004). Primer STS hasil pengembangan dari RAPD yang telah digunakan untuk mengidentifikasi varietas padi premium Jepang, Koshihikari (Ohtsubo et al, 2002) dan galur isogeniknya (Nakamura et al, 2004), digunakan dalam penelitian ini dan diobservasi pada varietas padi japonica dan indica.…”
Section: Pendahuluanunclassified
“…Marka STS atau SCAR yang dikembangkan dari RAPD (Jain et al, 2004) dianggap lebih reproducible dan mudah aplikasinya (Stewart dan Via, 1993). Marka STS hasil pengembangan dari RAPD berhasil mendiferensiasi padi japonica berdasarkan palatabilitas dan beras ketan (Ohtsubo et al, 2001).…”
Section: Analisis Genotipe Dengan Primer Sts Terpaut Palatabilitasunclassified
“…AFLP derived SCAR markers, SA598 on chromosome4 was found to be linked to the gall midge resistance gene, Gm7 in the rice cv. RP2333-156-8 (Sardesai et al 2002Jain et al 2004) identified an AFLP marker, AR257 and RAPD marker, AP19 587 on chromosome8 linked to the gall midge resistance gene, Gm8 in the rice cv. Jhitipiti.…”
Section: Introductionmentioning
confidence: 99%
“…Eight of the ten gall midge resistant genes have been tagged using various molecular markers (Nair et al 1995;Mohan et al 1997;Katiyar et al 2000Katiyar et al , 2001Sardesai et al 2002;Biradar et al 2004;Jain et al 2004). Since some of these markers were not useful in other breeding populations, additional closely linked SSR markers were identified .…”
Section: Introductionmentioning
confidence: 99%